Comparison of minimally invasive surfactant therapy with intubation surfactant administration and extubation for treating preterm infants with respiratory distress syndrome: a randomized clinical trial - Mohammad Kazem Sabzehei; Behnaz Basiri; Maryam Shokouhi; Sajad Ghahremani; Ali Moradi (The Korean Pediatric Society, 2022)
Background Respiratory distress syndrome (RDS) is a common cause of hospitalization and death in preterm infants who require surfactant treatment and respiratory support. Purpose This study aimed to compare the clinical outcomes of minimally invasive surfactant therapy (MIST) and the INtubation, SURfactant administration, and Extubation (INSURE) technique in preterm infants with RDS. Methods In this clinical trial, 112 preterm infants born at 28-36 weeks of gestation and diagnosed with RDS randomly received 200-mg/kg surfactant by MIST or the INSURE method. In the MIST group, surfactant was administered using a thin catheter (5F feeding tube); in the INSURE group, surfactant was administered after intubation using a feeding tube and the tracheal tube was removed after positive pressure ventilation was started. Nasal continuous positive airway pressure was applied in both groups for respiratory support and the postprocedure clinical outcomes were compared. Results The mean hospitalization time was shorter for infants in the MIST group than for those in the INSURE group (9.19± 1.72 days vs. 10.21±2.15 days, P=0.006). Patent ductus arteriosus was less frequent in the MIST group (14.3% vs. 30.4%, P=0.041). Desaturation during surfactant administration occurred less commonly in the MIST group (19.6% vs. 39.3%, P=0.023). There were no significant intergroup differences in other early or late complications. Conclusion These results suggest that surfactant administration using MIST could be a good replacement for INSURE in preterm infants with RDS since its use reduced the hospitalization time and the number of side effects.